Exports and domestic demand pressure: a dynamic panel data model for the euro area countries - Paulo Esteves; Eleina Bobeica; Antonio Rua; Karsten Staehr (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
The paper investigates the link between domestic demand pressure and exports by considering an error correction dynamic panel model for eleven euro area countries over the last two decades. The results sug- gest that there is a statistically signi cant substitution e ect between domestic and foreign sales. Furthermore, this relationship appears to be asymmetric, as the link is much stronger when domestic demand falls than when it increases. Weakness in the domestic market trans- lates into increased e orts to serve markets abroad, but, conversely, during times of boom, exports are not negatively a ected by increas- ing domestic sales. This reorientation towards foreign markets was particularly important during the crisis period, and thus could rep- resent a new adjustment channel to strong negative domestic shocks. The results have important policy implications, as this substitution ef- fect between domestic and external markets might allow the euro area countries under stress to improve their trade outcomes with a relatively small downward pressure on domestic prices.
Keywords: C22; C50; F10; 330